Analisis Kinerja dan Prospek Komoditas Udang Indonesia di Pasar Internasional - Marcelina Matilda Mingga Dalopez; Denny Saputera (Ekonomis: Journal of Economics and Business, 2026)
This study aims to provide a comprehensive overview of the performance and prospects of Indonesian shrimp exports in the international market during the 2019-2014 period. The quantitative methods used are the trade performance index (TPI), revealed comparative advantage (RCA), and constant market share (CMS). The results of this study reveal that the performance of Indonesian shrimp exports experienced very positive growth. The increasing export volume indicates the resilience and solid growth of the Indonesian shrimp sector amidst global market dynamics. Indonesia has a comparative advantage in shrimp exports, although still lagging behind India and Vietnam, this position indicates that Indonesian shrimp remains competitive in the global market. The study also found that competitiveness, product quality and certification, regulatory support, and export performance simultaneously influence the future prospects of Indonesian shrimp exports.